Dog Man unleashed - Pilkey, Dav 1966- (New York, NY Graphix, an imprint of Scholastic, 2017)
Dog Man pursues his out-of-control archnemesis Petey the cat, whose crime spree has taken the city by storm.
"Treehouse Comix proudly presents."
Chiefly illustrations.
Bklst 01/01/2017
SLJ Jan 2017
School Library Journal, January 2017
Booklist, January 2017
Keywords: Dogs -- Fiction; Police -- Fiction; Adventure fiction; Adventure stories; Humorous fiction; Humorous stories; Graphic novels; Pets; Animals; Adventure and adventurers -- Fiction; Humorous stories; Graphic novels